Gentrification and mental health inequities: a scoping review - Pineault, Justine; Blache-Pichette, Clara; Loignon, Christine; Shareck, Martine (Social science & medicine (1982), 2025)
The association between gentrification and general health has been established in the scientific literature. Less is known about the relationship between gentrification and mental health at a population level, and for specific subgroups. This scoping review aimed to document (1) the relationships between gentrification and mental health in the general population, and among specific social groups, and (2) the mechanisms which might explain why gentrification impacts the health of specific social groups more than others. A framework for understanding the pathways by which neighborhood gentrification may lead to mental health inequities guided the study. We included qualitative and quantitative studies published from 2000 to 2024 in English or French. We identified 40 peer-reviewed studies through database searches. A mix of positive and negative effects of gentrification on mental health were found in samples of adults, while only negative effects on mental health were found for children, young adults and older adults. A mix of positive and negative effects were found in samples of residents in gentrifying neighborhoods and for residents who had lived in a gentrifying neighborhood for more than 3 years. Only better mental health outcomes were found among gentrifiers, while only worse mental health outcomes were found among long-term and displaced residents. Findings from this scoping review can guide future research and urban planning as it documents gentrification's effects on mental health and explores why gentrification may impact the health of specific social groups more than others. •Gentrification's effects on mental health vary by residents' characteristics.•Studies only found positive mental health outcomes for gentrifiers.•Studies only found negative mental health outcomes for long-term residents.•Studies only found negative mental health outcomes for youth and older adults.•Low-income ethnic minorities and women were most affected by gentrification.